Persebaran Daerah Rawan Banjir Di Wilayah Tulungagung - Agil Wong H; Ahsanul In’am S; Alvi Wardatun N; Erni Yusnia; Sendryna Mey H; Hany Nurpratiwi (Universitas 45 Surabaya, 2023)
Flooding is a common problem that often occurs, so it requires early handling of areas that frequently occur in floods. According to the geographical location of Tulungagung is in the lowlands where this is a factor in the occurrence of flooding and this area is passed by the Brantas River. Tulungagung during the rainy season often floods. In addition, what is discussed in this study are (1) Definition of flooding (2) History of Tulungagung floods (3) Areas in Tulungagung which are prone to flooding (4) Efforts to deal with floods in the Tulungagung area (5) Causes of flooding in Tulungagung. The research conducted by our group aims to provide information about flood disasters and response efforts in the Tulungagung area. The research method used in this study is descriptive qualitative by providing a description in the form of the word flood and its handling. The type used in this research is descriptive interpretative. The place chosen in this study is the Tulungagung area. The subjects used in this study were the people of Tulungagung.